2017
DOI: 10.1186/s40807-017-0038-8
|View full text |Cite
|
Sign up to set email alerts
|

A review of optimum parameter values of a passive solar still and a design for southern Bangladesh

Abstract: Pure and fresh water is being scarce day by day. Although Bangladesh is a riverine country, pure drinking potable water is not a cheap commodity. Most of the people in the cities boil water to drink, and people of the villages take tube-well's water directly, which might have high amount of heavy metal like arsenic. Solar still is a cheap and very useful renewable technology, which can be used in Bangladesh extensively everywhere at the rooftop as a pure water source. Objective of this paper was to find a low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…According to Afrand et al (2016), Al-Hinai et al (2002), Elango et al (2015), Madhlopa and Johnstone (2009), Mowla and Karimi (1995), Nguyen et al (2017), Sarkar et al (2017), Selvaraj and Natarajan (2018), Varun (2010), and Xiao et al…”
Section: Heat Transfer On the Cover Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…According to Afrand et al (2016), Al-Hinai et al (2002), Elango et al (2015), Madhlopa and Johnstone (2009), Mowla and Karimi (1995), Nguyen et al (2017), Sarkar et al (2017), Selvaraj and Natarajan (2018), Varun (2010), and Xiao et al…”
Section: Heat Transfer On the Cover Surfacementioning
confidence: 99%
“…Many of such reports in the literature have demonstrated that the productivity and performance of solar stills depend on parameters like solar radiation, wind velocity, basin water depth, temperature difference between the cover plate and water, cover thickness, cover inclination, bottom insulation, and geometry of the equipment (Ayoub et al, 2015;Dunkle, 1961;Edalatpour et al, 2016;Gnanaraj & Velmurugan, 2019;Khalifa & Hamood, 2009;Kumar et al, 2015;Mowla & Karimi, 1995;Nguyen et al, 2017;Omara et al, 2017;Rahbar et al, 2015;Raj and Manokar, 2017;Rashidi et al, 2017;Rufuss et al, 2016;Sarkar et al, 2017;Selvaraj & Natarajan, 2018;Tayeb, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Various type of passive, active, single effect and multiple effect solar stills are assessed in [3]. Sarkar et al [4] performed an extensive literature review and discussed the optimum design parameters of passive solar stills for the prevailing climatic and operational conditions. Different techniques used for improving the efficacy of the inclined solar still have been argued in [5].…”
Section: Introductionmentioning
confidence: 99%
“…The difference between the two categories is that passive still basin is heated directly and without the involvement of any active element like heaters or boilers, but active stills have active heating elements. In other words, passive stills have a simple design and no extra heating system is required [10].…”
Section: Introductionmentioning
confidence: 99%